(untitled) (Journal of International Crisis and Risk Communication Research, 2020)
With the ongoing COVID-19 pandemic, we are facing another watershed moment for our field. There truly could not be a better time to be editing an open-access journal for the international community of risk and crisis communication scholars and practitioners. In this essay, we provide an update on the Journal’s status in terms of acceptance rates, global perspective, and readership rates.